Increase in Reproducibility of Research Results of Bioobject Cryopreservation - Gorbunov, L. V. (Problems of Cryobiology and Cryomedicine, 2010)
Conditions of reproducibility increase for cryobiological research results were examined with the proposed mathematical model. It has been shown that increase of reproducibility of research results is provided with taking into account the initial state of biological material and the efficiency of its using. Application of this mathematical model increases the reproducibility of research results up to 5 times that provides the obtaining significant result when reducing the biological material number to 25 times. Testing of the suggested model showed, that taking into account of initial state of bovine and carp spermatozoa and murine embryos increased reproducibility of results in average in 1.5 times, allowing the comparison of the results of various experiments.